Komunikasi Interpersonal Antara Terapis Dengan Anak Penyandang Adhd (Attention Deficit Hyperactivity Disorder)(Studi Deskriptif Kualitatif Pola Komunikasi Interpersonal - Nurhuda, Murti; , Drs. Joko Sutarso, M.Si (2016)
This study is to find out how the interpersonal communication between children with ADHD and the therapist in the Developmental Clinic Child and Adolescent Mental Hospital of Dr. RM. Soedjarwadi. The design of this study used a qualitative approach with descriptive method. Goal of this research is interpersonal communication between the therapist and the child with ADHD. Methods of data ollection in this study will use two methods: interview, and documentation. There are five subjects in this study, the Chairman Part, two speech therapists, and two occupational therapists. Data analysis technique used in 2 this research is interactive analysis. The conclusion in the study of patterns of Interpersonal Communication Children with ADHD with a therapist. Communications made by the therapist with ADHD is called therapeutic ommunication, namely: (1) The tone was firm and disampailan verbal and nonverbal. The therapist as a party initiative to compose and send messages. (2) Switching activity, therapists need to create a schedule that alternates between children prefer activities that patients with medical or therapeutic activity. (3) The distance interaction, expected therapist can maintain a safe distance when interacting with children. That is, the distance therapist with children with ADHD when communication is not too far or too close distance. (4) The eye contact, eye therapy parallel conduct when communicating with ADHD children with the goal of children to be more concentration again. Connection in this study is the use of non-verbal communication that includes hand gestures and body gesture. (5) Nice touch, the therapist when communicating with children with ADHD through touch and aims to provide comforts such as stroking the child's head.